Mechanism of aggregate reactivation by the molecular chaperone CLPB - Zhang, Ting (Kansas State University, 2012)
ClpB, a bacterial chaperone that belongs to the AAA+ protein family, cooperates with the Hsp70/40 system (DnaK, DnaJ and GrpE in E.coli) in the reactivation of aggregated substrates by translocating them through the central channel of its hexameric form. ClpB is essential for survival of bacteria under heat shock and plays an important role in the infectivity of pathogenic microorganisms. However the detailed mechanism of ClpB disaggregation activity is still not clear. ClpB is a multi-domain protein, which consists of two nucleotide binding domains (NBD1 and NBD2) connected by the middle domain (M domain), and the N-terminal domain connected to the rest of the protein by a flexible linker. In this work, mutations were introduced into the linker region to modify the mobility of the N-terminal domain. It was found that without altering the proper folding and oligomerization of ClpB, all the mutants had deficiencies in aggregate reactivation, possibly due to the weaker binding to aggregated substrates in the initial step of disaggregation. This led to the conclusion that the flexible attachment of the N-terminal domain supports substrate binding and controls the disaggregation by ClpB. Moreover, partial inhibition of the ClpB chaperone activity was observed for all the linker variants, suggesting that the linker sequence might have been optimized by selective pressure to maintain the optimal efficiency of aggregate reactivation. To study the substrate translocation of ClpB, a BAP (ClpB-ClpA P-loop) variant that binds to the protease ClpP was constructed. A FRET-based experiment was designed and the fluorescently-labeled ClpB substrates were produced. This work sets the stage for further studies on the mechanism of aggregate recognition by ClpB. ClpB also plays important roles in pathogenic bacteria invasion and virulence. Recombinant ClpB from Ehrlichia chaffeensis, a pathogenic bacterium that causes human monocytic ehrlichiosis, was purified to study its biochemical properties. Ehrlichia ClpB (Eh_B) and E.coli ClpB (Ec_B) sequences are highly conserved in the nucleotide binding region and poorly conserved in the N-terminal and M domain. The oligomerization, ATPase activity, chaperone activity and substrate binding of the recombinant Eh_B were tested. Recombinant Eh_B was able to reactivate aggregated proteins in the presence of HSP70 from E.coli with equal efficiency as Ec_B. However, the mechanism of Eh_B interactions with substrates and/or substrate specificity may be different from that of E. coli ClpB.
Keywords: Protein chaperone; ClpB; AAA+; Biochemistry (0487)